Pengaruh Desain Produk, Brand Image dan Kualitas Produk Terhadap Keputusan Pembelian Sepeda Motor Honda di Kabupaten Sumbawa - Muhammad Nizar; Aris Sugiarto (Jurnal Ilmiah Raflesia Akuntansi, 2025)
This study aims to analyze the influence of product design, brand image, and product quality on the purchasing decisions of Honda motorcycles among consumers in Sumbawa Regency. The study employs a quantitative associative method with data collected from 190 respondents through questionnaires. The data were analyzed using multiple linear regression and hypothesis testing. The results indicate that product design and product quality have a significant positive effect on purchasing decisions, while brand image does not have a significant impact. The coefficient of determination (R²) shows that 20.7% of the purchasing decision variability can be explained by these variables. The findings suggest that consumers prioritize the attractiveness and functionality of the product design and the reliability and performance of the motorcycle over brand image when deciding to purchase a Honda motorcycle in Sumbawa. This study provides valuable insights for marketers and manufacturers in formulating strategies to enhance consumer purchasing decisions by focusing on product innovation and quality improvement.